Analisis Peran Perpustakaan Dalam Menumbuhkan Kemampuan Literasi Informasi Siswa SD Negeri 02 Gendingan Kabupaten Tulungagung - Nugrananda Janttaka; Eka Yuliana Sari (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research purposes to know the role of library in build students information literacy skill at fourth grade of SD Negeri 02 Gendingan.This research uses qualitative research with 30 student at IV, V, And VI grade, 1 librarian and 3 classroom teacher of high grade. The research object is the role of library to build students literacy skill. The data collection of the research uses interview (fourth grade students, one librarian, one classroom teacher) and questionnaire and take documentation during pandemic, once of weeks. The result of research showed that the library has important role in build students literacy skill. The weakness of the role of the library lies in electronic sources such as computers for students that are not available in the library, so that the only sources of information that students get are printed sources. Students information literacy skills are also in accordance with information literacy skills standards that is, accessing information, evaluating information, and using information.